An analysis of US accounting firms' cross-country audit quality of China concepts stocks*. Issue 2 (2nd April 2016) - Jia, Nan; Li, Dan
Abstract: PCAOB once issued an article challenging US accounting firms' practice of outsourcing the audit of US-listed Chinese companies. By analysing China concepts stocks audited by US firms from 2001 to 2012, this paper seeks to find the optimal mode for cross-country auditing. The study shows that integration and alliance outsourcing have significantly higher quality than non-alliance outsourcing, although no significant difference has been found between the former two modes. However, as the length of cooperation extends, the audit quality of non-alliance outsourcing improves significantly, which remarkably narrowed its difference with alliance outsourcing. Moreover, for the integration mode, audit quality decreases significantly as client importance increases, and consequently reduces its superiority in audit quality over outsourcing. Hence, although both integration and alliance outsourcing are favourable for cross-country auditing in China, special attention should be paid to integration where firms may compromise audit independence for large clients.